Proposition of Cutoff Points for Anthropometric Indicators to Identify High Blood Pressure in Adolescents - Borges, Leandro Lima; Gerage, Aline Mendes; Monteiro, Luciana Zaranza; Ulbrich, Anderson Zampier; Silva, Diego Augusto Santos (Frontiers in Nutrition, 2022)
Aim To propose cutoff points for anthropometric indicators for high blood pressure (HBP) screening in adolescents and to identify, among these indicators, those more accurately for boys and girls. Methods This cross-sectional study was carried out in the city of São José, SC, Brazil with 634 adolescents aged 14 to 19 years. Blood pressure levels were measured using a digital oscillometric sphygmomanometer and adolescents were classified as having HBP or not. Anthropometric indicators were calculated based on anthropometric measurements such as body mass (BM), height, waist circumference (WC), hip circumference (HC) and triceps, subscapularis, suprailiac, and midcalf skinfold thickness (SF). The Receiver Operating Characteristic Curve (ROC) was used to analyze the predictive capacity of anthropometric indicators in the identification of HBP. Results Higher values of Area Under the Curve (AUC) were for the anthropometric indicators BM (0.67; 95%CI: 0.62–0.72), body mass index (BMI) (0.67; 95%CI: 0.62–0.72), and WC (0.67; 95%CI: 0.62–0.71) for males. For females, no anthropometric indicator had discriminatory power for HBP screening. The cutoff points for the anthropometric indicators with discriminatory power for HBP screening in males were BM > 64.80 Kg, BMI > 21.76 Kg/m2, fat percentage (FP) > 15.75, waist height to ratio (WHtR) > 0.41, WC > 73.00 cm, and HC > 92.25 cm. Conclusion Anthropometric indicators of body adiposity had greater discriminatory power of HBP screening in males. For females, caution is suggested because the anthropometric indicators showed AUC values (95%CI) below 0.60.